2020
DOI: 10.3390/ijms21062025
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Liquid Chromatography-Tandem Mass Spectrometry-Based 5-Plex Assay for Mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPSs) are rare lysosomal storage diseases caused by the accumulation of undegraded glycosaminoglycans in cells and tissues. The effectiveness of early intervention for MPS has been reported. Multiple-assay formats using tandem mass spectrometry have been developed. Here, we developed a method for simultaneous preparation and better measurement of the activities of five enzymes involved in MPSs, i.e., MPS I, MPS II, MPS IIIB, MPS IVA, and MPS VI, which were validated using 672 dried blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Detection of enzyme activity and GAGs levels in neonatal DBS samples by MS/MS, including two-layer screening of enzyme activity and combination of multiple GAGs, is helpful for early screening and diagnosis of MPSs [ 31 , 59 , 62 , 67 , 74 , 91 ]. Simultaneous measurement of multiple enzyme activities by MS/MS has revealed that the prevalence of diseases such as MPS I is higher than the estimates of clinical diagnosis [ 69 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Detection of enzyme activity and GAGs levels in neonatal DBS samples by MS/MS, including two-layer screening of enzyme activity and combination of multiple GAGs, is helpful for early screening and diagnosis of MPSs [ 31 , 59 , 62 , 67 , 74 , 91 ]. Simultaneous measurement of multiple enzyme activities by MS/MS has revealed that the prevalence of diseases such as MPS I is higher than the estimates of clinical diagnosis [ 69 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Determination of I2S activity can be performed using peripheral blood leukocytes, cultured skin fibroblasts, or dried blood spot samples. Since multiple sulfatase deficiency is also characterized by decreased I2S activity, it should be excluded by simultaneous measurement of other sulfatases to confirm I2S deficiency and the diagnosis of MPS II [ 20 , 21 , 22 ].…”
Section: Diagnosismentioning
confidence: 99%
“…This study was approved by the IRB at the local institutes and Nemours/AIDHC (IRB#: 281498). The method was adapted from another study from our lab [33].…”
Section: Dbs Samplesmentioning
confidence: 99%
“…Many groups, including our own, have reported a five-tier multiplex assay that can measure the enzyme activities for MPS I, II, IIIB, IVA, and VI simultaneously using tandem mass [31][32][33][34][35]. There are multiple methods for GAG analysis that have been summarized in detail by Kubaski et al and Khan et al [12,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation